Quantitative DNA analysis of low grade cervical intraepithelial neoplasia and human papillomavirus infection by static and flow cytometry. Issue 6606 (31st October 1987) - Watts, K C; Husain, O A; Campion, M J; Lorriman, F; Butler, E B; McCance, D; Jenkins, D; Singer, A
Abstract : Quantitative deoxyribonucleic acid (DNA) analysis of cervical biopsy specimens from 26 women with cytological, colposcopic, and histological evidence of mild cervical atypia consistent with cervical intraepithelial neoplasia grade I, reactive atypia, or human papillomavirus infection alone or in combination was performed in a comparative evaluation of Feulgen microspectrophotometry, the fast interval processor image analysis system, and flow cytometry. The fast interval processor image analysis system showed a distinct advantage over the other methods, being faster and allowing the operator to see the cells that were selected for measurement. The three methods of measurement together showed that the DNA content of at least 2% of the cells measured exceeded 5C (C being the haploid amount of DNA in a normal cell and 2C representing the diploid complement of a normal cell) in all cases of cervical intraepithelial neoplasia grade I and reactive atypia and in 87% of those reported as showing human papillomavirus infection alone. In contrast, the DNA content of cervical biopsy specimens from the transformation zone of 11 normal controls did not exceed 4C. This study shows the value of using a DNA threshold–that is, the "5C exceeding rate"–to distinguish between normal and neoplastic appearances of the cervix. These results support the view that cervical infection by human papillomavirus is a true precursor of neoplasia.